Ion-Pair Based Dispersive Liquid-Liquid Microextraction for Spectrophotometric Analysis of Carmoisine in Food: A BAGI and AGREE Study - Ismael Jabbar, Araf; Ismael Jabbar, Adel; Mahmoud Hussain, Arwa; Fahmi Abbas, Ruba; Fuente-Ballesteros, Adrián (Al-Nahrain Journal of Science, 2026)
This paper discusses the identification of a new dispersive Liquid-liquid microextraction method for evaluating carmoisine dye using spectrophotometry. It has been established that Carmoisine dye is an anionic azo food dye used in the food industry in some countries such as Iraq. This method involves the extraction of carmoisine from aqueous solutions using chloroform as the extraction solvent in a DLLME procedure. Parameters influencing the DLLME efficiency, including pH, type and volume of extraction as well as dispersive solvents (chloroform and ethanol), under a centrifugation conditions, were thoroughly optimized to complete extraction conditions. Moreover, the method showed a linear calibration curve in the range of 1.0-10.0 mg/L. The low values of both the limit of quantification (0.297 mg/L) and the limit of detection (0.099 mg/L) indicate a more sensitive DLLME method. The applicability and environmental impact of the developed method were assessed using the Blue Applicability Grade Index (BAGI) and the Analytical Greenness metric (AGREE), yielding scores of 70.0 and 0.55, respectively, indicating a practical method with moderate adherence to green analytic chemistry principles. The optimized DLLME procedure was successfully applied to the determination of carmoisine dye in various food samples.